Assessment of Bukavu Finalist Pupils' English Active Vocabulary Knowledge - TrÃ©sor, Mihigo Bienfait (FKIP - Universitas Tanjungpura, 2024)
The Congolese national program of English instructs that secondary school pupils be equipped with 2,000 active words in the four years of English training (based on 500 active words per year), so that they can be able to communicate effectively in English. However, the Congolese State Exams do not evaluate finalist pupils